Mapping Research Trends on Archives : A Bibliometric Study (Open Society Conference, 2024)
The development of archival research in Indonesia can be determined by carrying out bibliometric analysis. This research was conducted to provide a reference to researchers in the archival field regarding current trends in archival research. This research aims to explore the development of research in the field of archives from 2019 to 2024. Data obtained and processed from Google Scholar using Harzing's Publish and Perish (PoP) software amounted to 930 articles. Data analysis using VOSviewer visualization. The research results show that the most researched research theme is "archives management information systems". The research location most often used as a place for research is "government institutions/agencies". The most rapidly growing research trends are clusters related to "archival digitization", "website-based archives", and "archival electronic applications". Meanwhile, the themes of "static archives" and "archivists" are research themes that may be approaching saturation.